1975
DOI: 10.1037/h0076215
|View full text |Cite
|
Sign up to set email alerts
|

Systematic manipulation of individual events in a truly random control in rats.

Abstract: Truly random sequences of tone, conditioned stimuli (CSs), and shock, unconditioned stimuli (USs), were given to groups of rats; then conditioning to the OS was measured using a conditioned suppression procedure. In Experiment 1, eliminating chance CS-US pairings by systematically removing CSs that overlapped USs weakened conditioning monotonically as a function of the number of paired CSs removed. In Experiment 2, systematically delaying early chance pairings, while holding constant the number of CSs, USs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 12 publications
4
35
0
Order By: Relevance
“…In Experiment 1, a target CS was trained under conditions in which unsignaled USs were interspersed with target CS-US trials. Consistent with a variety of other behavioral observations under similar training conditions (e.g., Ayres et al, 1975;Durlach, 1983;Rescorla, 1968), a deficit in responding to the target CS was observed. Experiment 1 further revealed that this deficit in responding to a target CS could be attenuated in two different ways.…”
Section: Groupsupporting
confidence: 89%
“…In Experiment 1, a target CS was trained under conditions in which unsignaled USs were interspersed with target CS-US trials. Consistent with a variety of other behavioral observations under similar training conditions (e.g., Ayres et al, 1975;Durlach, 1983;Rescorla, 1968), a deficit in responding to the target CS was observed. Experiment 1 further revealed that this deficit in responding to a target CS could be attenuated in two different ways.…”
Section: Groupsupporting
confidence: 89%
“…A variety of experiments (e.g., Ayres, Benedict, & Witcher, 1975;Keller, Ayres, & Mahoney, 1977;Rescorla, 1972) have shown that the neutrality of a CSI and, presumably, the associated contextual excitation hold only asymptotically. Preasymptotically, both theory and data indicate that the CSI may acquire temporary associative strength due to random CS-US pairings.…”
Section: Resultsmentioning
confidence: 99%
“…In its molarity, comparator theory was similar to contingency theory (Rescorla, 1967), a theory that attempted to predict behavior based on molar contingencies or correlations between CSs and USs, correlations calculated over long spans of time including multiple sessions. That view, however, was challenged by the fact that different groups of rats could receive molar correlations of zero and yet respond to the CS or not at the time of testing depending on the molecular details of trial sequencing at the time of training (Ayres, Benedict, & Witcher, 1975;Benedict & Ayres, 1972). For explanation, such results appeared to require a theory such as the Rescorla-Wagner model, in which the molecular ordering of trial types was crucially important.…”
Section: Discussionmentioning
confidence: 99%